S Studi Farmakovigilans Efek Samping Multivitamin Dimasyarakat Palangka Raya - Khoirul Nur Pratiwi; Iwan Yuwindry; Onieqie Ayu Dhea Manto (LPPM Universitas Sari Mulia, 2020)
ABSTRACT Background: Multivitamins play an important role in the body to regulate activities in the body. One of the effects of taking excess multivitamins can cause poisoning or other adverse symptoms called hypervitaminosis. Objective: To find out what advers drug reactions occurred as a result and how many incidents of multivitamin use in children aged 5-11 years. Methods: This type of research uses descriptive observational with a cross sectional design. The research was conducted using the Naranjo algorithm, which distributes questionnaires online in the form of google from to social media and after being filled in by respondents, it will be sorted according to the inclusion criteria. Results: This study showed 36 samples that met the inclusion criteria, where demographic characteristics for the female gender were more dominant by 55.556%. Based on the age of respondents as much as 25% who consume multivitamins aged 11 years, and multivitamin type profiles that are widely used are curcuma plus 27,778%. The results of the Advers Drug Reaction incident were 5 respondents to Curcuma Plus, Imboost which caused abdominal pain by 2 respondents, and Muveron which caused nausea by 1 respondent. Based on the assessment with naranjo scores for respondents who experienced Advers Drug Reaction obtained 7 respondents in the Possible category and 1 respondent in the Probable category. one of the factors that influence such as how to consume it is not right. Conclusion: This study can conclude a causal description of the incidence of Advers Drug Reaction in respondents using multivitamins, 7 respondents in the Possible category and 1 respondent in the Probable category. Keywords: Advers Drug Reaction, Multivitamins, Naranjo